ChemInform Abstract: Oxidant‐ and Metal‐Free Synthesis of 4(3H)‐Quinazolinones from 2‐Amino‐N‐methoxybenzamides and Aldehydes via Acid‐Promoted Cyclocondensation and Elimination. Issue 5 (February 2015) - Cheng, Ran; Tang, Linlin; Guo, Tianjian; Zhang‐Negrerie, Daisy; Du, Yunfei; Zhao, Kang
Abstract Nitro‐group in either of the substrates leads to the formation of dihydroquinazolinone products which can be further transformed to the desired quinazolinones [cf.